AB0501 Retrospective Study of Multitarget Therapy with Combination of Mizoribine and Tacrolimus for Systemic Lupus Erythematosus with or without Nephritis. (10th June 2014) - Kukida, Y.; Kida, T.; Inoue, T.; Isoda, Y.; Sagawa, T.; Ishigaki, R.; Kasahara, A.; Nakabayashi, A.; Fujioka, K.; Nagahara, H.; Fujii, W.; Murakami, K.; et al.
Abstract : Background: Multitarget therapy for lupus nephritis which was reported by Bao et al. 1 is hopeful treatment option for refractory systemic lupus erythematosus (SLE). However, there are few studies about multitarget therapy with combination of prednisolone (PSL), purine synthesis inhibitor and calcineurin inhibitor for SLE. Objectives: The aim of this study is to evaluate efficacy and safety of multitarget therapy with combination of PSL, mizoribine (MZR) and tacrolimus (TAC) as induction or add-on therapy for refractory SLE with or without lupus nephritis. Methods: We retrospectively studied 26 SLE patients treated with multitarget therapy in our department from April 2009 to December 2013. The mean age was 44.5 years old and 23 patients were female. They were divided into two groups; (A) 10 patients who were initially treated with this therapy as induction, and (B) 16 patients who were additionally treated with this therapy due to minor flares or difficulty in reducing PSL dose. We evaluated efficacy and safety of this combination strategy as (A) induction therapy and (B) add-on therapy respectively. Results: (A) Five of 10 patients had lupus nephritis (2 were class IV and 3 were class IV+V). Three of 10 stopped this therapy due to severe adverse events within 12 months. Other 2 patients stopped this therapy due to preparation for pregnancy. Among nephritis patients, complete renal response rate at 6 months was 75%. The mean SLE disease activity index (SLEDAI) was reduced from 25 at baseline to 7.5 at 6 months. In all non-nephritis patients, their symptoms or blood examination data were improved. The mean SLEDAI was reduced from 14.4 at baseline to 2.4 at 6 months. (B) Five of 16 patients had lupus nephritis. One patient stopped this therapy due to preparation for pregnancy. The mean PSL dose was reduced from 14.8mg/day at baseline to 9.2mg/day at 12 months. The mean SLEDAI was reduced from 6.5 at baseline to 2.7 at 12 months. In all 26 patients, adverse events were 28 cases in the observation period. Most of these were mild infections. Three severe adverse events were observed. These were hypertrophic cardiomyopathy due to interaction of TAC and clarithromycin, nocardial soft tissue abscess and cryptococcal meningitis. All three patients who experienced severe adverse events were over 65 years old. Conclusions: The combination use of PSL, MZR and TAC is effective as induction therapy and as add-on therapy for refractory SLE regardless of having lupus nephritis. However, elderly patients tend to suffer from sever adverse events. References: Bao H et al: Successful treatment of class V+IV lupus nephritis with multitarget therapy, J Am Soc Nephrol 19; 2001-2010, 2008 Disclosure of Interest: Y. Kukida Grant/research support: Astellas Pharma Inc. Asahi Kasei Pharma Corp., T. Kida: None declared, T. Inoue: None declared, Y. Isoda: None declared, T. Sagawa: None declared, R. Ishigaki: None declared, A. Kasahara: None declared, A. Nakabayashi: None declared, K. Fujioka: None declared, H. Nagahara: None declared, W. Fujii: None declared, K. Murakami: None declared, T. Seno: None declared, A. Yamamoto Grant/research support: Astellas Pharma Inc. Asahi Kasei Pharma Corp., M. Kohno Grant/research support: Astellas Pharma Inc. Asahi Kasei Pharma Corp., Y. Kawahito Grant/research support: Astellas Pharma Inc. Asahi Kasei Pharma Corp. DOI: 10.1136/annrheumdis-2014-eular.3186